Comparative Genomic Analysis Reveals Novel Facts About Leptospirillum Spp. Cytochromes - Levican-Jaque, G; Chavez-Rosales, R (2012)
Chemolithoautotrophic acidophilic bacteria, which belong to the genus Leptospirillum, can only grow with Fe(II) as electron donor and oxygen as an electron acceptor. Members of this genus play an important role in bioleaching sulfide ores. We used nearly complete genome sequences of Leptospirillum ferrooxidans (group I), Leptospirillum rubarum, Leptospirillum 5-way CG (group II) and Leptospirillum ferrodiazotrophum (group III) to identify cytochromes that are likely involved in electron transfer chain(s). The results show the presence of genes encoding a number of c-type cytochromes (18-20 genes were identified in each species), as well as bd and cbb3 oxidases. Genes encoding cbb3 oxidase are clustered, with predicted genes involved in cbb3 maturation proteins. Duplication of cbb3 encoding genes (ccoNO) was detected in all four genomes. Interestingly, these micro-organisms also contain genes that potentially encode bc1and b6f-like complexes organized into two putative operon structures. To date, the Leptospirillum genus includes the only organisms reported to have genes coding for two different bc complexes. This study provides detailed insights into the components of electron transfer chains of Leptospirillum spp., revealing their conservation among leptospirilla groups and suggesting that there may be a single common pathway for electron transport between Fe(II) and oxygen. Copyright © 2012 S. Karger AG, Basel.